Consolidated evaluation of polysaccharide degradation after oil palm wood pretreatment with indigenous white-rot hymenomycetes - Naidu, Yuvarani; Shariffah-Muzaimah, S. A.; Nur-Rashyeda, R.; Idris, Abu Seman; Sundram, Shamala; Khairulmazmi, A.; Siddiqui, Yasmeen (Springer, 2022)
The oil palm industry is the backbone of the Malaysian economy. However, this industry is threatened by basal stem rot (BSR) caused by the fungus Ganoderma boninense, which has caused severe losses over the past several decades. The study reported here is part of an ongoing project to reduce Ganoderma inoculum and manage oil palm waste on plantations, which could be a green technology approach to reduce BSR infection pressure. A preliminary search for potential white-rot hymenomycetes to accelerate the degradation of oil palm stumps has been initiated. As a continuity, the present study was designed to comprehensively investigate the changes in wood crystallinity at different stages of oil palm wood degradation after pretreatment with three white-rot hymenomycete species. The findings were used to limit potential white-rot candidate(s) for their secretion of cellulolytic, hemicellulolytic and amylolytic enzymes, selectively or simultaneously, using principal component analysis. The overall per cent crystallinity of healthy wood decayed by Lentinus tigrinus increased as degradation proceeded. Conversely, crystallinity generally increased at 75 d in the diseased wood pretreated with Trametes lactinea, owing to the preferential degradation of noncrystalline lignins and hemicelluloses by this strain. Anatomical characterization revealed penetration of fungal mycelia into the degraded wood vessels, phloem and parenchymal tissues with microscopic cavities. In advanced stages of pretreatment, the loosening of the parenchymal tissue, including the wood rays, was more rapid in the diseased wood than in the healthy wood. This study provides new insights into the biochemical and anatomical changes initiated by white-rot hymenomycetes during the degradation of oil palm wood blocks. The present findings could be efficiently utilized for sustainable biological stump pretreatment, particularly with respect to the polysaccharide components of lignocellulosic materials.